Superposition and alignment of labeled point clouds - Fober, T.; Glinca, S.; Klebe, G.; Hüllermeier, Eyke (IEEE/ACM Transactions on Computational Biology and Bioinformatics)

Load Balancing in P2P Networks: Using Statistics to Fight Data and Execution Skew - Warneke, Daniel; Dannewitz, Christian (Journal of Advances in Information Technology)

Fuzzy sets in machine learning and data mining - Hüllermeier, Eyke (Applied Soft Computing Journal)

Top-down induction of fuzzy pattern trees - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Simulation of Deep Drawing of Carbon Fibre Prepregs - Hankeln, Frederik; Mahnken, Rolf (PAMM)

Werberecht (Gesetze, Urteile, Fälle und Lösungen, Sprachfassung auf interaktiver CD) - Krimphove, Dieter

A New Approach for Analyzing Convergence Algorithms for Mobile Robots - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (Automata, Languages and Programming)
Given a set of n mobile robots in the d-dimensional Euclidean space, the goal is to let them converge to a single not predefined point. The challenge is that the robots are limited in their capabilities. Robots can, upon activation, compute the positions of all other robots using an individual affine coordinate system. The robots are indistinguishable, oblivious and may have different affine coordinate systems. A very general discrete time model assumes that robots are activated in arbitrary order. Further, the computation of a new target point may happen much earlier than the movement, so that the movement is based on outdated information about other robot's positions. Time is measured as the number of rounds, where a round ends as soon as each robot has moved at least once. In [Cohen, Peleg: Convergence properties of gravitational algorithms in asynchronous robot systems], the Center of Gravity is considered as target function, convergence was proven, and the number of rounds needed for halving the diameter of the convex hull of the robot's positions was shown to be O(n^2) and Omega(n). We present an easy-to-check property of target functions that guarantee convergence and yields upper time bounds. This property intuitively says that when a robot computes a new target point, this point is significantly within the current axes aligned minimal box containing all robots. This property holds, e.g., for the above-mentioned target function, and improves the above O(n^2) to an asymptotically optimal O(n) upper bound. Our technique also yields a constant time bound for a target function that requires all robots having identical coordinate axes.

Die Auswirkung verschiedener Klebungen auf das Verhalten eines piezoelektrischen Wandlers - Bause, Fabian
Die Modellierung bzw. das virtuelle Design von Ultraschallwandlern spielt gerade im Hinblick auf die Mannigfaltigkeit ihrer Einsatzgebiete und die stetig wachsenden Anforderungen der Industrie eine Schlüsselrolle bei der Entwicklung piezoelektrischer Sensor- und Aktorsysteme. Der jeweils für eine spezielle Anwendung zu erreichende Grad der Realitätsnähe der eingesetzten Modelle ist dabei essentielle Voraussetzung für die Legitimation des virtuellen Designs. Neben idealisierten Strukturen, welche der Modellbildung unweigerlich anhaften, wird die Realitätsnähe wesentlich durch die genutzten Materialmodelle und deren Parametrisierung beeinflusst. Viele Arbeiten wurden aus diesem Grund auf dem Gebiet der akustischen Materialdaten-bestimmung sowohl passiver als auch aktiver Materialien durchgeführt. Ein Ultraschallwandler besteht nun aus einer Komposition von aktiven und passiven Elementen, welche z. B. mittels Klebungen zusammengefügt werden. Aktuelle Praxis ist die Vernachlässigung der Klebschichteigenschaften oder ggf. eine Korrektur der durch die Klebschichtdicke hervorgerufene Frequenzverschiebung durch eine virtuelle Vergrößerung eines der Fügeteile. Dabei werden die Koppelbedingungen zwischen den gefügten Materialien als ideal angenommen, was in der Realität jedoch nicht der Fall ist. Klebungen sind weder isotrop noch homogen aufgebaut. Des Weiteren ist ihre Dicke sehr klein, was in der Computersimulation dazu führt, dass sie über effektive Parameter und stark vereinfachte Modelle beschrieben werden.

Von der Messaufgabe zum Sensorsystem - Henning, Bernd
Ultraschallsensoren werden heute in der Industrie vielfach erfolgreich für die verschiedensten Messaufgaben eingesetzt und ständig weiterentwickelt. Wesentliche aktuelle Entwicklungen zielen auf die Erweiterung der Funktionalität (adaptierbare Abstrahlcharakteristik, scannende Sensoren …), die Erhöhung der Zuverlässigkeit, die Miniaturisierung sowie auf die Reduktion der Gerätekosten (Materialsubstitution) und Fertigungskosten (Konstruktion und Montage).

Ultrasonic Nondestructive Testing of composite materials using disturbed coincidence conditions - Bause, Fabian; Olfert, Sergei; Schröder, Andreas; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar (Journal of Electronic Measurement and Instrument)

Analyzing the effect of adhered metal electrodes on piezoelectric elements using different types of adhesives - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Modeling and simulation play a key-role in computer-assisted design of ultrasonic sensors. The accuracy of those numerical or analytical models highly depends on the material dataset chosen as well as on the digitized simplified geometry. Thus, researchers worked on techniques how to measure material datasets of piezoceramics or passive materials (i.e. polymers) for use in simulation [Rau08] [Rup09]. Most computer models neglect the influence of adhesive bonds between those active and passive material components used to form a complete ultrasonic transducer and thus imply perfect interface layers. To gain a more accurate model one need to go further and consider non-perfect interface layers between assembly parts. Because adhesive bonds are neither necessarily isotropic nor homogeneous and their geometric dimensions are very small, we need to define effective material datasets dependent on the model used in simulation. In this contribution the indicator under study is the electric impedance of the active element. We will show the influence of different adhesives used to adhere metal electrodes on piezoceramic discs. Therefore, we use several different types of adhesives (epoxies, cyanoacrylates and perfluorpolyether grease) and different sizes of piezoceramic discs (PIC 255, manufacturer: PI Ceramic GmbH) of the same batch (thickness, diameter). The electrodes have been cut from one plate made of stainless steel using a laser to avoid uncertainty effects due to variations in material-parameters. The probes have been prepared in an air-conditioned Lab with constant temperature and humidity. The indicators considered to identify the effect of those different adhesive films are extracted from the electric impedance of the electromechanical converter.

Ultrasonic distance sensors - An overview and trends - Henning, Bernd; Schröder, Andreas (Journal of Electronic Measurement and Instrument)
Nowadays ultrasonic distance sensors are widely used in automobiles, robotics and in industrial automation. Some functional principles of usable transducers for airborne ultrasonic distance measurements are shown. As every sensor principle, ultrasonic distance sensors have pros and cons which lead to some problems and challenges described below. For the main challenges (crosstalk and blind zone) some trends and solutions are presented.

Vergleich zwischen der Schlierenmethode nach Toepler und der Hintergrundschlierenmethode zur Bestimmung akustischer Grössen eines Ultraschallwandlers - Olfert, Sergei; Henning, Bernd
Es gibt unterschiedliche Methoden, um räumliche Schallwechseldruckverteilungen in Flüssigkeiten zu erfassen. Viele dieser Verfahren haben zwei Nachteile. Sie sind zum einen invasiv, beeinflussen somit die sich ausbreitende Ultraschallwelle, und zum anderen sehr zeitaufwendig. Die Visualisierung von Ultraschallfeldern mittels Schlierenmethode ist eine schnelle und einfache Methode, um zweidimensionale Schallfelder nichtinvasiv zu analysieren. Ein besonderer Vorteil besteht darin, dass man unmittelbar resultierende Veränderungen im Schallfeld zum Beispiel bei Frequenzänderung, Sensorausrichtung… beobachten kann. In diesem Beitrag werden zwei dieser Verfahren vorgestellt. Die modifizierte Schlierenmethode nach Toepler, das im Weiteren als modifizierte Schlierenmethode bezeichnet wird, und die Hintergrund-schlierenmethode, das sich bisher hauptsächlich zur Strömungsvisualisierung etabliert hat [1]. Im ersten Teil werden beide Messverfahren erläutert, die realisierten Messaufbauten sowie Einsatzmöglichkeiten für die Schallfeldcharakterisierung kurz vorgestellt. Im zweiten Teil werden beide Verfahren verglichen und die Vor- und Nachteile bezüglich ausgewählter Messaufgaben bewertet.

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter--thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

Luftultraschall-Abstandsmessung mit verkürztem Mindestabstand - Schröder, Andreas; Henning, Bernd
Bei der Luftultraschall-Abstandsmessung mit einem einzelnen Schallwandler ist der Mindestabstand durch die Sendesignaldauer und die Ausschwingzeit des Schallwandlers begrenzt. Daher führt die Verwendung von codierten Sendesignalen, wie sie z.B. für die Unterscheidung mehrerer Sender genutzt werden können, im Allgemeinen zu einer Vergrößerung des Mindestabstandes. Dieser Beitrag zeigt, dass der Mindestabstand bei codierten Sendesignalen durch eine geeignete Signalverarbeitung, bei der eine Trennung des Sende- und Empfangssignals erfolgt, deutlich verringert werden kann.

Model based separation of transmitted and received signal for single transducer distance measurement applications - Schröder, Andreas; Henning, Bernd
Simultaneous transmitting and receiving (STaR) enhances the utilization of single transducer ultrasound measurement systems. In distance measurement applications the dead zone can be reduced to nearly zero, independent of the transmitted signal. So it is possible to transmit codedsignals to identify different sensors without increasing the minimum distance. The electrical transducer signal consists of the electrical transmitted and received signal. A separation of these two signals can be done with a mathematical model of the electrical system. For this purpose it is necessary to digitize the electrical transducer signal. Due to the relative small amplitude of the received signal compared to the transmitted signal amplitude, a high resolution analog to digital converter (ADC) is needed. This leads to high requirements for the ADC. The necessary resolution limits the sample rate of the ADC. By down mixing the transducer signal using a coherent quadrature demodulation (CQD), as used in many high frequency ultrasound applications, the sample rate of the ADC can be reduced. In this contribution an airborne ultrasound distance measurement system with reduced dead zone is used to analyze the effects of this concept to the signal conditioning, system identification and system performance. The approach is compared with a system without CQD and an ADC with a lower resolution but a higher sample rate. By analyzing the pros and cons of both systems the usability of a CQD based system for a STaR application is evaluated. The distance measurement system used for the experiments is based on a 40 kHz airborne ultrasonic transducer. A gyrator based transmit amplifier delivers a system bandwidth of about 10 kHz. In the experiments, coded transmitted signals are used to measure the distance to a metal reflector. The main objectives are short distances between 0 mm and 200 mm. Here a separation of transmitted and received signal is necessary. The reflector distance is calculated by a cross correlation between transmitted and received signal.

Finite element simulation of single ultrasonic transducer with segmented electrodes to adjust the directional characteristic - Unverzagt, Carsten; Henning, Bernd
For many applications like level measurement and industry robotics it is of advantage if the directional characteristic of an ultrasonic transducer is changeable or adaptable for the improvement of spatial resolution. Often this goal is reached with the use of ultrasonic transducer arrays, which elements are driven with phase shifted excitation signals. One disadvantage of these solutions is the great effort for building such an array and the multi-channel sensor electronics. In this contribution the directional characteristic of a single air transducer with segmented electrodes is analyzed. Therefore a variable script based finite element model is used to discover the influence of different electrode configurations on the directional characteristic of a single piezoceramic transducer. Especially the influence on the angle of beam and the near field length are evaluated. The used variable model permits an optimization of the configuration with regards to the mentioned criteria. The findings will be used for the development of a level measurement system for bulk solids.
Keywords: Elektrode

Robuster Selbsttest mit Diagnose - Cook, Alejandro; Hellebrand, Sybille; Indlekofer, Thomas; Wunderlich, Hans-Joachim (5. GMM/GI/ITG Fachtagung "Zuverlässigkeit und Entwurf")

An exact algorithm for F-measure maximization - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (In Proceedings NIPS-2011, 25th Annual Conference on Neural Information Processing Systems, Granada, Spain)

Preference-based policy iteration: Leveraging preference learning for reinforcement learning - Cheng, W.; Fuernkranz, J.; Hüllermeier, Eyke; Park, S.H. (Proceedings ECML/PKDD-2011, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Athens, Greece,)

Learning from label preferences - Fürnkranz, J.; Hüllermeier, Eyke (in Proceedings DS-2011, 14th International Conference on Discovery Science, number 6926 in LNAI)

Learning monotone nonlinear models using the Choquet integral - Fallah Tehrani, A.; Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2011, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Athens, Greece,)

Preference-based CBR: First steps toward a methodological framework - Hüllermeier, Eyke; Schlegel, P. (In Proceedings ICCBR-2011, 19th International Conference on Case-Based Reasoning, number 6880 in LNAI)

Anwendungsszenarien als Werkzeug zur (V) Ermittlung des Nutzens von corporate social software - Trier, Matthias; Richter, Alexander; Mörl, Susanne; Koch, Michael (10th International Conference on Wirtschaftsinformatik)

CYBEREMOTIONS – Collective Emotions in Cyberspace - Ahn, Junghyun; Borowiec, Anna; Buckley, Kevan; Cai, Di; Chmiel, Anna; Czaplicka, Agnieszka; Dąbrowski, Grzegorz; Garas, Antonios; Garcia, David; Gobron, Stéphane; Hillmann, Robert; Hołyst, Janusz; et al. (Procedia Computer Science)

Dynamische Analyse von Netzwerken elektronischer Kommunikation. Kann der Zentralität getraut werden? - Trier, Matthias; Bobrik, Annette (Netzwerkanalyse und Netzwerktheorie)

Anwendungsszenarien als Werkzeug zur (V)Ermittlung des Nutzens von Corporate Social Software - Richter, Alexander; Mörl, Susanne; Trier, Matthias; Koch, Michael

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)

Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Preserving Charge and Oxidation State of Au(III) Ions in an Agent-Functionalized Nanocrystal Model System - Müllegger, Stefan; Schöfberger, Wolfgang; Rashidi, Mohammad; Lengauer, Thomas; Klappenberger, Florian; Diller, Katharina; Kara, Kamuran; Barth, Johannes V.; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold (ACS Nano)

Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Microscopic structure and energy transfer of vacancy-related defect pairs with Erbium in wide-gap semiconductors - Konopka, A.; Greulich-Weber, S.; Dierolf, V.; Jiang, H.X.; Gerstmann, Uwe; Rauls, E.; Sanna, S.; Schmidt, Wolf Gero (Optical Materials)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Driving forces for the adsorption of cyclopentene on InP(001) - Favero, P.P.; Ferraz, A.C.; Schmidt, Wolf Gero; Miotto, R. (Surface Science)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Methane adsorption on graphene from first principles including dispersion interaction - Thierfelder, C.; Witte, M.; Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Bipartite ranking through minimization of univariate loss - Kotlowski, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2011, 28th International Conference on Machine Learning, Washington, USA)

Memory Virtualization for Multithreaded Reconfigurable Hardware - Agne, Andreas; Platzner, Marco; Lübbers, Enno (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL))

Design and architectures for dependable embedded systems - Henkel, Jörg; Hedrich, Lars; Herkersdorf, Andreas; Kapitza, Rüdiger; Lohmann, Daniel; Marwedel, Peter; Platzner, Marco; Rosenstiel, Wolfgang; Schlichtmann, Ulf; Spinczyk, Olaf; Tahoori, Mehdi; Bauer, Lars; et al. (Proceedings of the seventh IEEE/ACM/IFIP International Conference on Hardware/software Codesign and system synthesis - CODES+ISSS '11)

Complex Queries in P2P Networks with Resource-Constrained Devices - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Advances in Information Technology)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, G.; Hahn, W.; Widhalm, A.; Zrenner, A.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Combined ab initio and classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Barium titanate ground- and excited-state properties from first-principles calculations - Sanna, S.; Thierfelder, C.; Wippermann, S.; Sinha, T. P.; Schmidt, Wolf Gero (Physical Review B)

Modellbasierte Konzipierung eines hybriden Energiespeichersystems für ein autonomes Schienenfahrzeug - Gausemeier, Jürgen; Dumitrescu, Roman; Tschirner, Christian; Stille, Karl Stephan Christian (Tag des Systems Engineering)
Die Kommunikations- und Informationstechnik eröffnet neue Möglichkeiten zur Erweiterung und Optimierung der Systemfunktionalität mechatronischer Systeme. Die erfolgreiche Entwicklung dieser fortgeschrittenen mechatronischen Systeme bedarf sowohl einer besonderen Strukturierung der Informationsverarbeitung als auch einer geeigneten modellbasierten Entwurfstechnik. SysML und CONSENS eignen sich für den Entwurf derartiger Systeme. Die Anwendung von CONSENS wird anhand eines Demonstrators vertieft.
Keywords: Produktentstehung; HES; Hybrider Energiespeicher; CONSENS; SysML; SFB614; LEA-Publikation; Eigene

Aus dem Deutschen ins Italienische: U. Dirk und A. Wagner, Filosofia dell’interpretazione. Principi, sviluppi, caratteristiche

Aus dem Deutschen ins Italienische: G. Abel, Il rapporto interno tra linguaggio, comunicazione, mondo della vita e scienza

Adorno, T. W., Einführung in die Dialektik, Frankfurt a.M. 2010 - Ficara, Elena (Hegel-Studien)

Skeptizismus und Philosophie. Kant, Fichte, Hegel - Ficara, Elena (Rivista di storia della filosofia)

Metaphysik in der zeitgenössischen Hegelrezeption - Ficara, Elena (Hegel Jahrbuch)

Die Begründung der Philosophie im Deutschen Idealismus

Optimierte Regelung für mobile Elektromotoren - Wallscheid, Oliver; Peters, Wilhelm; Böcker, Joachim (Aktuelle Technik)

Current controller with defined dynamic behavior for an interior permanent magnet synchronous motor - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IECON 2011-37th Annual Conference of the IEEE Industrial Electronics Society)

What determines influenza vaccination take-up of elderly Europeans? - Schmitz, Hendrik; Wübker, Ansgar (Health Economics)

Direct evidence of risk aversion as a source of advantageous selection in health insurance - Schmitz, Hendrik (Economics Letters)

Why are the unemployed in worse health? The causal effect of unemployment on health - Schmitz, Hendrik (Labour Economics)

Profit efficiency and ownership of German hospitals - Herr, Annika; Schmitz, Hendrik; Augurzky, Boris (Health Economics)

Digital Control Strategy for Multi-Phase Interleaved Boundary Mode and DCM Boost PFC Converters - Grote, Tobias; Figge, Heiko; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Energy Conversion Congress and Exposition (ECCE))

Overcurrent Protection for the LLC Resonant Converter with Improved Hold-Up Time - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. 26th IEEE Applied Power Electronics Conference (APEC))

Unidirektionaler AC-AC-Matrixkonverter mit Dreipunkt Ein- und Ausgangsstufe - Schafmeister, Frank; Kolar, Johann

Verfahren zum spannungslosen Schalten der Pulswechselrichter-Ausgangsstufe eines indirekten Dreiphasen-AC-AC Matrixkonverters - Schafmeister, Frank; Kolar, Johann

Thermal-electrical modeling and simulation of resonantly operated DC-DC converters based on extended describing function method - Lv, J.; Cao, Z.; Fröhleke, N.; Böcker, Joachim; Yuan, H.; Mi, H. (Proceedings of the 2011 14th European Conference on Power Electronics and Applications)

Control Realization for an Interior Permanent Magnet Synchronous Motor (IPMSM) in Automotive Drive Trains - Peters, W.; Huber, T.; Böcker, Joachim (PCIM 2011, Nürnberg, Deutschland)

Logik und Mathematik in der Philosophie Leonard Nelsons - Peckhaus, Volker (Leonard Nelson – ein früher Denker der Analytischen Philosophie. Ein Symposium zum 80. Todestag des Göttinger Philosophen)

Robert and Hermann Grassmann’s Influence on the History of Formal Logic - Peckhaus, Volker (Hermann Graßmann. From Past to Future: Graßmann’s Work in Context. Graßmann Bicentennial Conference, September 2009)
Rezension: Zbl. Math. 1223.01014 (J. Mackenzie).

Leibniz’ Logik und die sprachliche Erschließung der Welt in der Moderne - Peckhaus, Volker (Departure for Modern Europe. A Handbook of Early Modern Philosophy (1400–1700))

Einleitung: Räume zwischen Materialisierung und Idealisierung - Peckhaus, Volker; Wahrig, Bettina (Berichte zur Wissenschaftsgeschichte)

Frequency / duty cycle current-mode fuzzy control for LCC resonant converter - Hu, M.; Böcker, Joachim; Fröhleke, N. (EPE2011, Birmingham, UK)

Modelling Lexical Alignment in Spontaneous Direction Dialogue Data by Means of a Lexicon Network Model - Mehler, Alexander; Lücking, Andy; Menke, Peter (Proceedings of 12th International Conference on Intelligent Text Processing and Computational Linguistics (CICLing))
We apply a network model of lexical alignment, called Two-Level Time-Aligned Network Series, to natural route direction dialogue data. The model accounts for the structural similarity of interlocutors’ dialogue lexica. As classification criterion the directions are divided into effective and ineffective ones. We found that effective direction dialogues can be separated from ineffective ones with a hit ratio of 96% with regard to the structure of the corresponding dialogue lexica. This value is achieved when taking into account just nouns. This hit ratio decreases slightly as soon as other parts of speech are also considered. Thus, this paper provides a machine learning framework for telling apart effective dialogues from insufficient ones. It also implements first steps in more fine-grained alignment studies: we found a difference in the efficiency contribution between (the interaction of) lemmata of different parts of speech.

Corpus-driven development of a Gesture Typology based on the Bielefeld Speech and Gesture Alignment Corpus - Hahn, Florian; Menke, Peter (Online Proceedings of the Corpus Linguistics 2011 Conference, Birmingham (UK))
We introduce the multimodal Bielefeld Speech and Gesture Alignment (SaGA) corpus, its design, structure, and approaches to a data-driven development and validation of a gesture typology.

The Bielefeld Jigsaw Map Game (JMG) Corpus - Lücking, Andy; Abramov, Olga; Mehler, Alexander; Menke, Peter (Online Proceedings of the Corpus Linguistics 2011 Conference, Birmingham (UK))

From Neural Activation to Symbolic Alignment: A Network-Based Approach to the Formation of Dialogue Lexica - Mehler, Alexander; Lücking, Andy; Menke, Peter (Proceedings of the International Joint Conference on Neural Networks (IJCNN 2011))

From Experiments to Corpora: The Ariadne Corpus Management System - Menke, Peter; Mehler, Alexander (Online Proceedings of the Corpus Linguistics 2011 Conference, Birmingham (UK))

Untersuchung alternativer Erwärmungsverfahren für den Presshärteprozess - Marten, Thorsten; Niewel, J.; Tröster, Thomas (HTM Journal of Heat Treatment and Materials)

Volker Remmert/Ute Schneider, Eine Disziplin und ihre Verleger. Disziplinenkultur und Publikationswesen der Mathematik in Deutschland, 1871–1949. Bielefeld: transcript Verlag 2010 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Mechanical Properties of Fused Deposition Modeling Parts Manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker (ANTEC)
In this work the influence of the orientation and the toolpath generation of manufactured parts based on the mechanical data are analyzed. Tensile Specimen are generated with the given parameters as well as with changing parameters of the native software based upon the CAD data. The parts then are built up with the “Fortus 400mc” from Stratasys. First tensile tests show different strength and strain characteristics that depend on the given structure and as a result of the build direction. The influence of the parameters was analyzed with a statistic test method by using the software Design Expert.

FPGA-Based High Performance AC Drive - Mathapati, S.

A Smelly Body, The Fear of the Unclean Feminine Body: A Cultural Analysis of the Debate on Perversion in Charlotte Roche’s Feuchtgebiete - Lammer, Christina (The Evil Body)

Portfolioarbeit im Fremdsprachenunterricht – Yes, we can! - Ballweg, Sandra; Bräuer, Gerd (Fremdsprache Deutsch 45/2)

Schreibend lehren lernen – unterstützt durch ein digitales Kompetenzportfolio für Lehramtsstudierende (dikopost) - Ballweg, Sandra; Scholz, Nadine; Richter, Kristina; Bruder, Regina (Schreibarrangements in Schule, Studium, Beruf)

Schreibberatung für internationale Studierende - Ballweg, Sandra (Sprachlernberatung für DaF)

Das Europäische Sprachenportfolio im Kontext des Rahmenplans Deutsch als Fremdsprache - Ballweg, Sandra (Deutsche Lehrer im Ausland 1)

Portfolioarbeit im Praxistext – Zeitverschwendung oder Wunderinstrument? - Ballweg, Sandra (Fremdsprache Deutsch 45/2)

Internationale Publikationen und gute Lehre? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Mastermodule. - Lück, Sonja (Herausforderung Internationalisierung)

Fachsprachlichkeit in Lehrbüchern. Korpuslinguistische Analysen von Fachtexten der beruflichen Bildung - Niederhaus, Constanze

Zur Förderung des Verstehens logischer Bilder in mehrsprachigen Lernergruppen; Essen ProDAZ. Deutsch als Zweitsprache in allen Fächern - Niederhaus, Constanze

„Oh Gott, was ist denn das hier alles?“ Evaluation von Lehr- und Lernmaterialien im Bereich der arbeitsplatzorientierten Grundbildung - eine Diskussion methodischer Vorgehensweisen - Niederhaus, Constanze (Lernprozesse in Alphabetisierung und Grundbildung Erwachsener. Diagnostik, Vermittlung, Professionalisierung)

Informierende Bilder in Fachkundebüchern: berufsfeldabhängige Variation und didaktische Konsequenzen - Niederhaus, Constanze (bwp@ Berufs- und Wirtschaftspädagogik - online, Ausgabe bwp@ Spezial 5 - HT2011)

AlphaZ Evaluation. Abschlussbericht AlphaZ Evaluation - Badel, Steffi; Niederhaus, Constanze

AlphaZ Evaluation. Sachbericht 2010 - Badel, Steffi; Niederhaus, Constanze

Frege, Gottlob, "Grundgesetze der Arithmetik. Begriffsschriftlich abgeleitet. Band I und II. In moderne Formelnotation transkribiert und mit einem ausführlichen Sachregister versehen von Thomas Müller, Bernhard Schröder und Rainer Stuhlmann-Laeisz", Mentis: Paderborn 2009 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Künne, Wolfgang, "Die Philosophische Logik Gottlob Freges. Ein Kommentar. Mit den Texten des Vorwortes zu Grundgesetze der Arithmetik und der Logischen Untersuchungen I–IV", Klostermann: Frankfurt a.M. 2010 (Klostermann Rote Reihe; 30) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

"Logik in der Philosophie", hg. v. Wolfgang Spohn/Peter Schroeder-Heister/Erik J. Olsson, Synchron: Heidelberg 2005 (Philosophische Impulse; 6) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Arai, Toshiyasu, “Progress in the Proof Theory Related to Hilbert’s Second Problem”, In: Sugaku Expositions 57 (2008), 83–96 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Cerroni, Cinzia, “Some Models of Geometries after Hilbert’s Grundlagen”, In: Rendiconti di Matematica (VII) 39 (2010), 47–66 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hausdorf, Felix, "Gesammelte Werke, Bd. VIII: Literarisches Werk", hg. v. Friedrich Vollhardt und Udo Roth, Springer: Berlin/Heidelberg 2010 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Deutsch als Fremdsprache. Zeitschrift zur Theorie und Praxis des Deutschunterrichts für Ausländer (Heft 2/ Rezensiert von Piirainen, Elisabeth) - Ptashnyk, Stefaniya

Das Wörterbuch der ukrainischen Sprache von Borys Hrinčenko - Ptashnyk, Stefaniya (Große Lexika und Wörterbücher Europas: Europäische Enzyklopädien und Wörter-bücher in historischen Porträts (Handbuchartikel))

Enzyklopädie der Ukrainekunde. Hg. von Volodymyr Kubijovyč - Ptashnyk, Stefaniya (Große Lexika und Wörterbücher Europas: Europäische Enzyklopädien und Wörter-bücher in historischen Porträts (Handbucharti-kel))

Deutsches Rechtswörterbuch und sein Nutzen für die historische Semantik-Forschung - Ptashnyk, Stefaniya (Historische Semantik. Jahrbuch für germanistische Sprachgeschichte)